Esophageal contractility increases and gastroesophageal reflux does not worsen after lung transplantation. Issue 10 (10th May 2019) - Posner, Shai; Finn, Raymond T; Shimpi, Rahul A; Wood, Richard K; Fisher, Deborah; Hartwig, Matthew G; Klapper, Jacob; Reynolds, John; Niedzwiecki, Donna; Parish, Alice; Leiman, David A
SUMMARY: Gastroesophageal reflux and esophageal dysmotility are common in patients with advanced lung disease and are associated with allograft dysfunction after lung transplantation. The effect of transplantation on reflux and esophageal motility is unclear. The aim of this study was to describe the changes in esophageal function occurring after lung transplantation. A retrospective cohort study was performed on lung transplant candidates evaluated at a tertiary care center between 2015 and 2016. A total of 76 patients who underwent lung transplantation had high-resolution manometry and ambulatory pH-metry before and after transplant. Demographic data, esophageal function testing results, and clinical outcomes such as pulmonary function testing were collected and analyzed using appropriate statistical tests and multivariable regression. Of the 76 patients, 59 (78%) received a bilateral transplant. There was a significant increase in esophageal contractility posttransplant, with an increase in median distal contractile integral from 1470 to 2549 mmHg cm s ( P < 0.01). There were 19 patients with Jackhammer esophagus posttransplant, including 15 patients with normal motility pretransplant. Nine patients with ineffective or fragmented peristalsis pretransplant had normal manometry posttransplant. Abnormal pH-metry was observed in 35 (46%) patients pretransplant and 29 (38%) patients posttransplant ( P = 0.33). Patients with gastroesophageal reflux disease posttransplant had less improvement in pulmonary function at one year, as measured by forced expiratory volume ( P = 0.04). These results demonstrate that esophageal contractility increases significantly after lung transplantation, with an associated change in motility classification. In comparison, gastroesophageal reflux does not worsen, but is associated with worse pulmonary function, posttransplant.